AKTIVITAS FISIK SEBAGAI ALTERNATIF MODEL PEMBELAJARAN YANG MENYENANGKAN: SEBUAH KAJIAN LITERATUR - Hermahayu Hermahayu; Robiul Fitri Mashitoh (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2022)
Fun learning is one of the principles applied in the independent curriculum. Learning needs to be designed by considering the stage of development and level of achievement of students, according to learning needs, and reflecting the characteristics and development of diverse students so that learning becomes meaningful and fun. The purpose of this study is to offer physical activity-based cognitive stimulation as a fun learning model. The method used is a literature review. The results showed that physical activity had a physiological effect on the body which ultimately had an impact on the child's cognitive function and the positive emotions felt by the child. Through this article, it is hoped that it can provide knowledge for teachers in designing physical activity-based learning activities as a fun learning model for students. In addition, schools can also collaborate with parents in developing programs of fun learning activities through the involvement of physical activities at home.